1983
DOI: 10.1159/000272872
|View full text |Cite
|
Sign up to set email alerts
|

Why Are There Old People

Abstract: Biological theories of adaptation are used to generate a model of human cognitive development in which physiological and cognitive changes in aged persons can be understood as an adaptive stage of development in its own right. These changes, within an appropriate societal context, make elderly individuals better able to perform certain tasks, or at least uniquely able to provide them, in ways which increase group survival. Emphasis is given to tasks involving oral transmission of information, especially in sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…For example, in one study, Adams, Smith, Pasupathi, and Vitolo (2002) found that older adults were more sensitive than younger adults to the testing context and that age differences in story recall observed under standard laboratory test conditions were attenuated when participants were instructed to tell the story to a young child. This latter situation is consistent with the knowledge transmission goal that is often associated with old age (e.g., Mergler & Goldstein, 1983). …”
Section: Aging the Costs Of Cognitive Engagement And Motivationsupporting
confidence: 85%
“…For example, in one study, Adams, Smith, Pasupathi, and Vitolo (2002) found that older adults were more sensitive than younger adults to the testing context and that age differences in story recall observed under standard laboratory test conditions were attenuated when participants were instructed to tell the story to a young child. This latter situation is consistent with the knowledge transmission goal that is often associated with old age (e.g., Mergler & Goldstein, 1983). …”
Section: Aging the Costs Of Cognitive Engagement And Motivationsupporting
confidence: 85%
“…Whereas retaining a greater proportion of information processed for fitness-relevance may have been adaptive for prehistoric children and younger adults who had (or would eventually have) the capacity to reproduce (Aslan & Bäuml, 2012; Nairne et al, 2007), it may not have been as functional for the older adults who were past their reproductive prime. Instead, this group would have likely served different societal roles (e.g., preserving and transmitting knowledge, preserving social connections; Mergler & Goldstein, 1983), perhaps shifting their priorities away from fitness goals and toward a more reflective/evaluative approach (Mather, 2010). Because the scenario used in the present studies makes explicit reference to food gathering, locating shelter and other resources, and predator avoidance, it is possible that such actions are less relevant to older adults because of differences in their evolutionary roles within social groups.…”
Section: Discussionmentioning
confidence: 99%
“…Basic cognitive resources (such as memory span and processing speed) tend to decrease with age (Salthouse, 1996a), creating a need for a more “economic” use of available resources. Age‐related changes in Need for Closure are also implicitly predicted by goal theories that propose a shift in social‐cognitive goals from young adulthood to the more mature years (Labouvie‐Vief, 1990; Mergler & Goldstein, 1983). In younger adulthood, knowledge acquisition goals are more salient (e.g., training for a new job), and the importance of obtaining accurate knowledge and information outweighs the costs of ambiguity.…”
Section: Conservatism and Cognitive Stylementioning
confidence: 99%